2008
DOI: 10.1179/174328108x271484
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on microstructures and properties of B containing cast steel for wear resistance applications

Abstract: The microstructures of B bearing cast steel (B steel) containing 0?8-1?2 wt-%B, 0?8-1?2 wt-%Cr, 1?0-1?5 wt-%Mn, 0?6-1?0 wt-%Si and 0?10-0?25 wt-%C have been characterised by means of optical microscopy, scanning electron microscopy, electron probe microanalyser and X-ray diffraction. The solidification structure of B steel consists of pearlite, ferrite, martensite and boride (Fe 2 B), while the hardness is 1430-1480 HV. Borides distribute along the grain boundary in the form of eutectic. Fine lath martensite a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 16 publications
1
9
0
1
Order By: Relevance
“…Meanwhile, for the martensite matrix in Fe-B cast alloy and Cr15 white cast iron, the SiC abrasive can easily cut into the matrix. Even for the eutectic (Cr, Fe) 7 C 3 carbides in Cr15 white cast iron with the hardness of 1,370-1,450 HV [22], the tested carbides can also be broken by abrasion particles in the form of micro cutting. Figure 14 shows the worn surfaces of Cr15 white cast iron and C 5 alloy under 50 N load.…”
Section: Heat Treatment Microstructure and Hardness Of Fe-b Cast Alloymentioning
confidence: 97%
“…Meanwhile, for the martensite matrix in Fe-B cast alloy and Cr15 white cast iron, the SiC abrasive can easily cut into the matrix. Even for the eutectic (Cr, Fe) 7 C 3 carbides in Cr15 white cast iron with the hardness of 1,370-1,450 HV [22], the tested carbides can also be broken by abrasion particles in the form of micro cutting. Figure 14 shows the worn surfaces of Cr15 white cast iron and C 5 alloy under 50 N load.…”
Section: Heat Treatment Microstructure and Hardness Of Fe-b Cast Alloymentioning
confidence: 97%
“…Some researchers have reported that the addition of boron element in the high chromium cast steel can increase the hardness and improve the abrasion resistance of high chromium cast steel [11,12]. The proper boron concentration in the low alloy cast steel benefits to obtain high hardness boride and improves the wear resistance of cast steel [13,14], which also reduces the addition of scarce nickel, molybdenum, and tungsten elements, and therefore decrease the production cost of wear resistant cast steel.…”
Section: Introductionmentioning
confidence: 97%
“…In the specimen with B doping, ∼2.5 m sized B-rich second phase particles precipitated. These particles can be found even after aging for 200 h at 500 • C. Microprobe analysis shows the composition of these particles to be (FeAl) 2 B. Fu et al also found that the water-quenching can induce the formation of eutectic Fe 2 B along the grain boundaries in B-containing cast steels [12]. These particles were not found in specimens without B doping.…”
Section: Methodsmentioning
confidence: 91%
“…This is due to the precipitation of boride particles in the B-doped specimen. Fu et al [12] also found that the borides distributed along the grain boundaries can enhance the hardness and strength. After water-quenching and aging for 200 h, the B-doped steel sustains a plastic strain of about 8% before failure, compared with ∼1% for the B-free steel.…”
Section: Figurementioning
confidence: 95%